Spectral CT and its specific values in the staging of patients with non-small cell lung cancer: technical possibilities and clinical impact. Issue 6 (June 2019) - Fehrenbach, U.; Kahn, J.; Böning, G.; Feldhaus, F.; Merz, K.; Frost, N.; Maurer, M.H.; Renz, D.; Hamm, B.; Streitparth, F.
Abstract : AIM: To investigate how spectral computed tomography (SCT) values impact the staging of non-small cell lung cancer (NSCLC) patients. MATERIALS AND METHODS: One hundred and thirteen patients with confirmed NSCLC were included in a prospective cohort study. All patients underwent single-phase contrast-enhanced SCT (using the fast tube voltage switching technique, 80–140 kV). SCT values (iodine content [IC], spectral slope pitch, and radiodensity increase) of malignant tissue (primary and metastases) and lymph nodes (LNs) were measured. Adrenal masses were evaluated in a virtual non-contrast series (VNS). If pulmonary embolism was present, pulmonary perfusion was analysed as an additional finding. RESULTS: Fifty-two untreated primary NSCLC lesions were evaluable. Lung adenocarcinoma had significantly higher normalised IC (NIC: 19.37) than squamous cell carcinoma (NIC: 12.03; p= 0.035). Pulmonary metastases were not significantly different from benign lung nodules. A total of 126 LNs were analysed and histologically proven metastatic LNs (2.08 mg/ml) had significantly lower IC than benign LNs (2.58 mg/ml; p= 0.023). Among 34 adrenal masses, VNS identified adenomas with high sensitivity (91%) and specificity (100%). In two patients, a perfusion defect due to pulmonary embolism was detected in the iodine images. CONCLUSION: SCT may contribute to the differentiation of histological NSCLC subtypes and improve the identification of LN metastases. VNS differentiates adrenal adenoma from metastasis. In case of pulmonary embolism, iodine imaging can visualise associated pulmonary perfusion defects. Highlights: SCT provides additional information about tumor tissue in lung cancer staging. Iodine content helps in the histological differentiation of primary tumors. SCT values improve the identification of lymph node metastases. Virtual non-contrast series differentiates between adrenal adenoma and metastases. In tumor-associated pulmonary embolism, lung perfusion defects are visualized in iodine imaging.